Mendidik Anak-Anak Yang Bermoral Rohani di Era Teknologi Informasi Sesuai Dengan Iman Kristen - Nainupu, Astrid Maryam Yvonny (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
The development of technology has a great influence on the spiritual morals of children. In this case, the role of parents, churches, and Christian schools is enormous. Based on theoretical studies and practical experiences, this paper aims to explain how parents, churches, and schools can play a major role in developing children's spiritual morals amid the onslaught of information technology. The method used is literature research based on biblical studies and practical studies based on experiences from parents at GKT New Life Semarang and Kindergarten Bintang Nusantara Banyumanik. This study concludes that parents, churches, and schools can build children's belief in the Bible's value through storytelling. Furthermore, social communication through family altars, online meetings for worship and fellowship, or private conversations for evangelism is also good to do. In addition, parents must be role models for children in spiritual matters, and the church must play a role in equipping parents. Christian teachers also need to be equipped to educate the children they are educated. Meanwhile, for teaching about the impact of technology, parents must firmly set boundaries and be an example. In addition, the church can also give lectures on the use of technology by the principles of the Christian faith and use it to preach the gospel. In schools, teachers must also provide teaching about the impact of technology and utilize technology as an attractive learning medium for children.